A novel Diameter-Selective functionalization of SWCNTs with lithium alkynylides - Gebhardt, Benjamin; Graupner, Ralf; Hauke, Frank; Hirsch, Andreas (European Journal of Organic Chemistry, 2010)
Covalent functionalization by addition to the sidewalls of single-walled carbon, nanotubes (SWCNTs) is one of the most important methods for the derivatization of carbon nanotubes. The nucleophilic addition of organometallic reagents (carbon- and nitrogen-based carbanions) has recently become a widely used tool for the introduction of functional moieties onto the surface of this new carbon allotrope. The extension, of this concept by the successful, nucleophilic addition of in situ generated lithium acetylides to the SWCNT scaffold is presented herein. The chemically derivatized SWCNTs have been characterized, in detail by TGA/MS, Raman, UV/Vis/NIR and fluorescence spectroscopy. On the basis of a detailed examination of the signals in the radial breathing-mode region of the Raman spectra, the preferred functionalization of smaller-diameter tubes has been clearly demonstrated. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Carbon nanotube sidewall functionalization with carbonyl compounds-modified birch conditions vs the organometallic reduction approach - Gebhardt, Benjamin; Syrgiannis, Zois; Backes, Claudia; Graupner, Ralf; Hirsch, Andreas; Hauke, Frank (Journal of the American Chemical Society, 2011)
Covalent addition reactions turned out to be one of the most important functionalization techniques for a structural alteration of single walled carbon nanotube (SWCNT) scaffolds. During the last years, several reaction sequences based on an electrophilic interception of intermediately generated SWCNT carbanions, obtained via Birch reduction or by a nucleophilic addition of organometallic species, have been developed. Nevertheless, the scope and the variety of potential electrophiles is limited due to the harsh reaction conditions requested for a covalent attachment of the functional entities onto the SWCNT framework. Herein, we present a significant modification of the reductive alkylation/arylation sequence, the so-called Billups reaction, which extends the portfolio of electrophiles for covalent sidewall functionalization to carbonyl compounds-ketones, esters, and even carboxylic acid chlorides. Moreover, these carbonyl-based electrophiles can also be used as secondary functionalization reagents for anionic SWCNT intermediates, derived from a primary nucleophilic addition step. This directly leads to the generation of mixed functional SWCNT architectures, equipped with hydroxyl or carbonyl anchor groups, suitable for ongoing derivatization reactions. A correlated absorption and emission spectroscopic study elucidates the influence of the covalent sidewall functionalization degree onto the excitonic transition features of carbon nanotubes. The characterization of the different SWCNT adducts has been carried out by means of Raman, UV-vis/nIR, and fluorescence spectroscopy as well as by thermogravimetric analysis combined with mass spectrometry and X-ray photoelectron spectroscopy analysis. © 2011 American Chemical Society.

Raman bands of nano-graphene flakes on carbon nanotubes after oxidation - Laudenbach, Jan; Gebhardt, Benjamin; Syrgiannis, Zois; Hauke, Frank; Hirsch, Andreas; Maultzsch, Janina (physica status solidi (b), 2013)
We present the Raman bands of nano-graphene flakes (NG flakes) produced by oxidation of single-walled carbon nanotubes. These bands overlap with the defect-induced Raman modes of carbon nanotubes. This can lead to an overestimation of the defect density in the nanotubes. Here we analyze the line shape and the dispersion of this superimposing Raman band of NG flakes. Furthermore, we investigate the predicted Raman band of NG flakes next to the high-energy Raman modes (G- and G+) of the nanotubes. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Reductive retrofunctionalization of single-walled carbon nanotubes - Syrgiannis, Zois; Gebhardt, Benjamin; Dotzer, Christoph; Hauke, Frank; Graupner, Ralf; Hirsch, Andreas; Hauke, Frank (Angewandte Chemie International Edition, 2010)
(Figure Presented) As if nothing had happened: A detailed mechanistic investigation of the nucleophilic addition of organolithium reagents onto single-walled carbon nanotubes (SWCNTs) revealed that the initial functionalization step is part of an equilibrium. Consequently, the functionalization of the sidewalls of SWCNTs is reversible, and the introduced substituents can be detached easily by reduction. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA.

Resonant Raman scattering on carbon nanotubes covalently functionalized with lithium decyne - Müller, Matthias; Meinke, Reinhard; Maultzsch, Janina; Gebhardt, Benjamin; Hauke, Frank; Hirsch, Andreas; Thomsen, Christian (physica status solidi (b), 2010)
We present resonant Raman measurements on single-walled carbon nanotubes covalently functionalized with lithium decyne. We study the influence of the functional moieties on the optical transitions of the nanotubes. From the extracted resonance profiles of the radial breathing modes the chiral indices of the corresponding tubes are assigned. Slight red shifts of the optical transitions are observed, which implies only a little charge transfer due to the chemical reaction. The reaction shows a pronounced diameter dependence as previously observed for comparable reactions with different addends.Carbon nanotubes covalently functionalized with decyne moieties. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Selective polycarboxylation of semiconducting single-walled carbon nanotubes by reductive sidewall functionalization - Gebhardt, Benjamin; Hof, Ferdinand; Backes, Claudia; Müller, Matthias; Plocke, Thomas; Maultzsch, Janina; Thomsen, Christian; Hauke, Frank; Hirsch, Andreas (Journal of the American Chemical Society, 2011)
The efficient and controllable synthesis, the detailed characterization, and the chemical postfunctionalization of polycarboxylated single-walled carbon nanotubes SWCNT(COOH) are reported. This innovative covalent sidewall functionalization method is characterized by (a) the preservation of the integrity of the entire σ-framework of SWCNTs; (b) the possibility of achieving very high degrees of addition; (c) control of the functionalization degrees by the variation of the reaction conditions (reaction time, ultrasonic treatment, pressure); (d) the identification of conditions for the selective functionalization of semiconducting carbon nanotubes, leaving unfunctionalized metallic tubes behind; (e) the proof that the introduced carboxylic acid functionalities can serve as versatile anchor points for the coupling to functional molecules; and (f) the application of a subsequent thermal degradation step of the functionalized semiconducting tubes leaving behind intact metallic SWCNTs. Functional derivatives have been characterized in detail by means of Raman, UV-vis/nIR, IR, and fluorescence spectroscopy as well as by thermogravimetric analysis combined with mass spectrometry, atomic force microscopy, and zeta-potential measurements. © 2011 American Chemical Society.